Acid-Catalyzed, Metal- and Oxidant-Free C=C Bond Cleavage of Enaminones: One-Pot Synthesis of 3,4-Dihydroquinazolines - Ting Chen; Ting Huang; Moudan Ye; Jinhai Shen (Molecules)
In this study, we present the HOAc-catalyzed selective cleavage of the C=C double bond of enaminones, enabling the formation of a new C–N bond and a new C=N bond for the one-pot synthesis of 2-substituted 3,4-dihydroquinazolines directly from ynones and 2-(aminomethyl)anilines. This method operates in ethanol under transition-metal-free and oxidant-free conditions, offering a sustainable and efficient approach for the synthesis of 3,4-dihydroquinazolines with broad functional group tolerance.